Differential Responses of Dimorphic Seeds and Seedlings to Abiotic Stresses in the Halophyte Suaeda salsa - Zhang, Hao; Hu, Mingfang; Ma, Hongyuan; Jiang, Li; Zhao, Zhenyong; Ma, Jinbiao; Wang, Lei (Frontiers in Plant Science, 2021)
The period between seed germination and seedling establishment is one of the most vulnerable stages in the life cycle of annuals in the saline environments. Although germination characteristics of Suaeda salsa seeds have been reported, the comparative germination patterns of dimorphic seeds and seedling growth to different abiotic stresses remain poorly understood. In this study, germination responses of dimorphic seeds to light and temperature were compared. Meanwhile, responses of dimorphic seeds and thereafter seedlings of S. salsa to different concentrations of NaCl and Na2SO4 were also tested. The results showed that the light did not significantly affect germination percentage of brown seeds, but significantly promoted germination of black seeds. Brown seeds could reach high germination percentage over a wide temperature range, however, germination of black seeds gradually increased with the increase of temperature. Brown seeds had higher germination percentage and velocity than black seeds under the same salt conditions. However, black seeds had higher recovery germination than brown seeds when transferred to deionized water. Young seedlings had lower salt tolerance than germinating seeds. At the same concentrations, Na2SO4 had stronger inhibitory effect on seed germination and seedling growth than NaCl. This study comprehensively compared germination traits of dimorphic seeds and seedling growth of S. salsa, and then developed a conceptual model to explain their adaptation to harsh saline environment.